Autophagy regulates long‐term cross‐presentation by murine dendritic cells. Issue 4 (10th February 2021) - Ho, Nataschja I.; Camps, Marcel G. M.; Verdoes, Martijn; Münz, Christian; Ossendorp, Ferry
Abstract: Autophagy has been reported to be involved in supporting antigen cross‐presentation by dendritic cells (DCs). We have shown that DCs have the ability to store antigen for a prolonged time in endolysosomal compartments and thereby sustain MHCI antigen cross‐presentation to CD8 + T cells. In the current study, we investigated the role of autophagy in long‐term antigen presentation. We show that the autophagy machinery has a negative impact on storage of antigen in DCs. Atg5 –/– DCs which are deficient in autophagy or DCs treated with common autophagy inhibitors showed enhanced antigen storage and antigen cross‐presentation. This augmented antigen cross‐presentation effect is independent of altered proteasome enzyme activity or MHCI surface expression on DCs. We visualized that the storage compartments are in close proximity to LC3 positive autophagosomes. Our results indicate that autophagosomes disrupt antigen storage in DCs and thereby regulate long‐term MHCI cross‐presentation. Abstract : Protein antigen‐antibody complexes are efficiently taken up by dendritic cells and conserved in storage compartments for prolonged antigen cross‐presentation to CD8 + T cells. LC3‐positive autophagosomes can breakdown antigen storage compartments thereby regulating the cross‐presentation capacity of dendritic cells.